Minangkabau Matriliny and Gender Equality: Cultural Contribution to Sustainable Development Goals - Putiviola Elian Nasir; Abdul Halim; Tanty Herida; Silvi Cory; Anita Afriani Sinulingga; Aditya Mukhti; Bunga Sri Hidayat; Faraytodi Gibran (Department of International Relations, Universitas Andalas, 2021)
The Minangkabau ethnic group is still the largest matrilineal society in the world. Past research on this ethnicity are mainly centralized on the concept of merantau (migration), on its adaptation after the enter of Islam, and on the gender role and position in Minangkabau society. This research aims to highlight the contribution of the Minangkabau matrilineal system to the local development of West Sumatra, specifically the gender equality goal of the Sustainable Development Goals (SDGs); and to what extent if it were present. This research employed qualitative method, and data were collected through literature study and interview with national and local NGOs working in the field of women and development. This research discovered that theoretically, the Minangkabau matrilineal values can and should stimulate the gender equality SDGs achievement in West Sumatra. However, in reality, gender inequality still exists in West Sumatra with several SGD targets having wider gaps compared to other patrilineal societies in Indonesia. This research argues that by not wholly implementing the matrilineal values, the West Sumatran Minangkabau people has indirectly restrained themselves from achieving gender equality in the region, specifically related to violence and discrimination against women, also active participation of women in the economy and politics.